Working from home and health complaints: on the difference between telework and informal overtime at home - Mergener, Alexandra [Verfasser]; Stawarz, Nico [Verfasser]; Rüger, Heiko [Verfasser]; Laß, Inga [Verfasser] (My University, 2025)
„Background: With the increase in the prevalence of working from home (WFH), understanding its impact on health has become more relevant. However, the possibility that health effects may depend on the specific WFH arrangement has largely been ignored in research. Objective: The aim of this study is to offer a differentiated view of WFH by distinguishing between informal overtime at home and telework during recognized working time when assessing its associations with mental and physical health complaints. Moreover, the extent of telework is considered. The study also differentiates the group of WFH non-users by distinguishing between voluntary non-use and employer-directed non-use. Methods: We apply OLS regression models with clustered standard errors by occupation to probability-based survey data that is representative of employees in Germany. The analytical sample was restricted to employees whose job tasks could be performed at home (N = 10,365). Results: Compared to employer-directed non-users, working informal overtime at home is associated with more mental health complaints, while telework is associated with fewer mental and physical health complaints. However, the beneficial association between recognized telework and mental health only applies to employees with relatively small extents of telework. At higher extents of telework, the mental health advantages disappear, while those for physical health tend to remain. Conclusion: This study suggests that a nuanced look at patterns of use and non-use of WFH is essential when gauging its impact on health.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 2.3.1 Arbeitsteilung & -organisation; G 2.3.3 Arbeitsformen, Techniken; 370; 610; Arbeitsgestaltung; Telearbeit; Auswirkung; Gesundheit; Gesundheitsschutz; Rechtliche Regelungen